Dietary Iodine Intake and Pattern of Thyroid Disorders among the Ethnic Population of Eastern Himalayan Ranges of India - Trisha Sonowal; Jatin Sarmah; Paresh Kumar Sarma (Archives of Medicine and Health Sciences)
Background and Aim: In the present study, dietary iodine intake and thyroid functioning were assessed among the ethnic adolescent group of Eastern Himalayan range with the hypothesis that insufficient iodine intake negatively affects normal thyroid functions. The aim of the study was to see the prevalence and relation between iodine deficiency and thyroid functioning. Materials and Methods: It is a hospital-based study conducted in the health care facilities of Dima Hasao district, Assam, from April 2021 to March 2022. The study included 821 subjects including both male and female of adolescent age group (10–19 years). The thyroid profiling, anti-Thyroid peroxidase antibody (anti-TPO Ab), and urinary iodine content (UIC) were carried out. Thyroid hormone analysis was carried out by chemiluminescence assay. The anti-TPO Ab was determined using the electrochemiluminescence immunoassay analyzer. The dietary iodine intake was measured on the basis of UIC and was determined by arsenic cerium catalytic spectrophotometry method by the Sandell-Kolthoff reaction. Results: The prevalence of thyroid disorder among the studied population was found to be 13.8%. Among different conditions of thyroid disorders, hypothyroidism was present in 10.6% and hyperthyroidism in 3.13%. 4.18% had elevated anti-TPO Ab. Among the euthyroid subjects with different thyroid disorders, 1.48% and 21% had anti-TPO Ab positivity, respectively. The median UIC was 99.97 µg/l. 25.78% of the population had iodine deficiency. Thyroid disorders were common in subjects with iodine deficiency (61.34%) than iodine sufficient subjects (20%). Conclusion: The work was an attempt to demonstrate how the dietary iodine intake influences thyroid functioning among the adolescent ethnic population of Eastern Himalayas which is manifested as high prevalence of subclinical hypothyroidism with iodine deficiency. The work underscores region specific recommendation on iodine supplementation for populations living in geographically remote locations.